Selecting Sport Events to Serve Public Policy Agendas - Taks, Marijke; Misener, Laura (Université d'Ottawa | University of Ottawa, 2016)
In this case, a local Sport Tourism Officer has been asked to prepare a recommendation for Evex City Council regarding which type(s) of event(s) the city should bid for, based on their public policy agenda of enhancing tourism for economic development purposes, and stimulating sport participation for residents. A questionnaire, a codebook, and a data set from two events, an international figure skating event and a provincial gymnastics event, are provided to assist in making a decision. The data set includes the spectators’ identification with and motives for attending the events, tourism activities they participated in, as well as some socio-demographic variables. Analyses of the data and interpretation of the results should assist the sport tourism officer in providing accurate recommendations to policy makers. Theories and frameworks that underpin this case include: public policy schemas; identity, motives and tourism behavior of event attendees; sport participation outcomes from sport events; leveraging; and event portfolios.
Keywords: Attendees; Events; Motivation; Sport participation; Sport tourism; Statistics